Remarks on a construction of Duistermaat - Small, Anthony (MATHEMATICA SCANDINAVICA, 2004)
A construction of Duistermaat’s, in which an auxiliary holomorphic curve in the line bundle O(4) on P_1 is associated to a minimal surface in R^3, is described in a new way and generalised to minimal surfaces in R^n. If the minimal surface is complete and has finite total curvature then the auxiliary curve is algebraic.